Isolated microgrid design using hybrid renewable energy with a multidirectional electronic converter and multiports to power remote health centers - Tisza Contreras, Juan Francisco (2023)
This article has two fundamental aspects to consider, one of them is the one that corresponds to guaranteeing the energy supply for a basic health center, using generation with renewable energy resources, in this case, what is proposed is to supply the loads with all the sufficient electrical energy to guarantee the continuous operation of the health center, photovoltaic and wind sources are considered in this work; The second point to consider is related to the analysis, design, and simulation of electronic power converters, especially looking for their bidirectional operation and focusing their study on both the power stage and the control stage. Important elements that are considered are advanced control strategies, in addition to being complemented with energy storage systems. In all cases, we use the IGBTs as devices used in the hardware implementation. Matlab, Simulink, as well as PSIM are used for simulations and tests.